Immunotherapy in endometrial cancer - an evolving therapeutic paradigm. Issue 1 (May 2015) - Longoria, Teresa; Eskander, Ramez
Abstract Endometrial cancer is the only gynecologic malignancy with a rising incidence and mortality. While cure is routinely achieved with surgery alone or in combination with adjuvant pelvic radiotherapy when disease is confined to the uterus, patients with metastatic or recurrent disease exhibit limited response rates to cytotoxic chemotherapy, targeted agents, or hormonal therapy. Given the unmet clinical need in this patient population, exploration of novel therapeutic approaches is warranted, and attention is turning to immunomodulation of the tumor microenvironment. Existing evidence suggests that endometrial cancer is sufficiently immunogenic to be a reasonable candidate for active and/or passive immunotherapy. In this review, we critically examine what is known about the microenvironment in endometrial cancer and what has been learned from preliminary immunotherapy trials that enrolled endometrial cancer patients, encouraging further attempts at immunomodulation in the treatment of aggressive forms of this disease.